2021
DOI: 10.15620/cdc:101761
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Mortality in the United States, 1999-2019

Abstract: Data Brief describing trends in suicide deaths by specific means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
414
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(429 citation statements)
references
References 1 publication
10
414
0
5
Order By: Relevance
“…Suicide rates among autistic women are reported to be much higher than in other clinical and non-clinical populations (Cassidy et al, 2014; Hirvikoski et al, 2019). And, in contrast to general population trends that show women are less likely than men to die by suicide (Hedegaard et al, 2018), autistic women are just as likely, if not more likely, to die by suicide as autistic men (Hirvikoski et al, 2016; Kirby et al, 2019). It is not well understood if and how internal distress and suicidality impact the daily functioning (e.g., performing work tasks, maintaining relationships, and engaging with the community) of autistic women (Howlin & Magiati, 2017; Kirby et al, 2016; Taylor et al, 2015); evidence from non-clinical and majority-male autistic samples suggests that the impact may be significant and negative (Katon, 2009; Wallace et al, 2016).…”
mentioning
confidence: 74%
“…Suicide rates among autistic women are reported to be much higher than in other clinical and non-clinical populations (Cassidy et al, 2014; Hirvikoski et al, 2019). And, in contrast to general population trends that show women are less likely than men to die by suicide (Hedegaard et al, 2018), autistic women are just as likely, if not more likely, to die by suicide as autistic men (Hirvikoski et al, 2016; Kirby et al, 2019). It is not well understood if and how internal distress and suicidality impact the daily functioning (e.g., performing work tasks, maintaining relationships, and engaging with the community) of autistic women (Howlin & Magiati, 2017; Kirby et al, 2016; Taylor et al, 2015); evidence from non-clinical and majority-male autistic samples suggests that the impact may be significant and negative (Katon, 2009; Wallace et al, 2016).…”
mentioning
confidence: 74%
“…Regarding other tested moderating variables, the results on gender were surprising, especially given the rich literature on gender differences on STBs and NSSI. For STBs, previous studies show mixed results in the association between gender and suicide, such that men are at higher risk of suicide (Hedegaard et al, 2018), while other studies have found comparable risks between genders (Kaplan et al, 2012). Similarly, for the gender difference on NSSI, some studies have found that women are more likely to engage in NSSI (see for a review, Bresin and Schoenleber, 2015), while other researchers have found no differences in engagement between genders (e.g., Garisch and Wilson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the lack of volume for many search strings, this may further decrease the reliability of search strings’ time series. Relatedly, as the overall suicide has risen over the past two decades, the relative percentage of death by firearm suicide has slightly declined from 61.7% in 1999 (Curtin et al, 2016) to just over 50% (Hedegaard et al, 2020). However, age‐adjusted firearm suicide rates increased during 2006–2018 among males (from 10.3 to 12.6 per 100,000) and females (from 1.4 to 1.9) (Curtin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a 35% increase in U.S. suicide rates over the past two decades (Hedegaard et al, 2020). Several potential explanations have been put forth, including the economy (Chang et al, 2013), opioid use (Bohnert & Ilgen, 2019), and increased firearm ownership (Anestis & Houtsma, 2018; Barber & Miller, 2014; Siegel & Rothman, 2016).…”
Section: Introductionmentioning
confidence: 99%